2019
DOI: 10.26434/chemrxiv.11336852.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and Styrene Copolymerization of Novel Dihalogen Ring-Substituted Isopropyl Cyanophenylacrylates

Abstract: <p>Novel dihalogen ring-substituted isopropyl 3-phenyl-2-cyanoacrylates, RPhCH=C(CN)CO<sub>2</sub>CH(CH<sub>3</sub>)<sub>2</sub> (where R is 2,5-dibromo, 3,5-dibromo, 2,3-dichloro, 2,4-dichloro, 2,5-dichloro, 2,6-dichloro, 3,4-dichloro, 3,5-dichloro, 2,4-difluoro, 2,5-difluoro, 2,6-difluoro) were prepared and copolymerized with styrene. The acrylates were synthesized by the piperidine catalyzed Knoevenagel condensation of ring-disubstituted benzaldehydes and isopropyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 11.8 and 30.4 mol% of IPCA is present in the copolymers, which is indicative of relatively high reactivity of the IPCA monomers towards ST radical which is typical of halogen ring-substituted different esters PCA [17][18][19][20][21][22][23][24][25]. Since IPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated IPCA monomer (y = 1) units alternating with short ST The copolymers prepared in the present work are all soluble in ethyl acetate, THF, DMF and CHCl3 and insoluble in methanol, ethyl ether, and petroleum ether.…”
Section: Synthesis and Characterization Of Styrene -Ipca Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 11.8 and 30.4 mol% of IPCA is present in the copolymers, which is indicative of relatively high reactivity of the IPCA monomers towards ST radical which is typical of halogen ring-substituted different esters PCA [17][18][19][20][21][22][23][24][25]. Since IPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated IPCA monomer (y = 1) units alternating with short ST The copolymers prepared in the present work are all soluble in ethyl acetate, THF, DMF and CHCl3 and insoluble in methanol, ethyl ether, and petroleum ether.…”
Section: Synthesis and Characterization Of Styrene -Ipca Copolymersmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [15][16][17] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization a number of methyl and oxy ringsubstituted PCAs, such esters as methyl [18,19], ethyl [20], propyl [21][22][23], propyl [24], and butyl [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [16][17][18] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization of a number of dichloro and difluoro ringsubstituted methyl [19][20][21], ethyl [22], propyl [23][24][25], isopropyl [26,27], butyl [28,29], isobutyl [30,31], and 2-methoxyethyl [32] PCAs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [15][16][17] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization a number of methyl and oxy ringsubstituted PCAs, such esters as methyl [18][19][20], ethyl [21], propyl [22][23][24], isopropyl [25][26][27], and butyl [28][29].…”
Section: Introductionmentioning
confidence: 99%